2014
DOI: 10.1002/14651858.cd003747.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Heparin for the prevention of venous thromboembolism in acutely ill medical patients (excluding stroke and myocardial infarction)

Abstract: The data from this review describe a reduction in the risk of DVT in patients presenting with an acute medical illness who receive heparin thromboprophylaxis. This needs to be balanced against an increase in the risk of bleeding associated with thromboprophylaxis. The analysis favoured LMWH compared with UFH, with a reduced risk of both DVT and bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 70 publications
(4 reference statements)
5
63
1
5
Order By: Relevance
“…These include patient willingness to accept prophylaxis and the tendency of physicians not to discontinue a prior prophylaxis prescription . The low incidence of venous thromboembolic events we observed (symptomatic deep vein thrombosis, 0.5%) is consistent with that reported in acutely ill bedridden medical inpatients, both in randomized trials and real‐life settings , and confirms previous perceptions concerning palliative care patients . In our view, these findings suggest that very few terminally ill patients are likely to be disturbed by symptoms of venous thromboembolism, a conclusion not supporting the concept that by decreasing such symptoms, thromboprophylaxis may improve a patient's quality of life.…”
Section: Discussionsupporting
confidence: 85%
“…These include patient willingness to accept prophylaxis and the tendency of physicians not to discontinue a prior prophylaxis prescription . The low incidence of venous thromboembolic events we observed (symptomatic deep vein thrombosis, 0.5%) is consistent with that reported in acutely ill bedridden medical inpatients, both in randomized trials and real‐life settings , and confirms previous perceptions concerning palliative care patients . In our view, these findings suggest that very few terminally ill patients are likely to be disturbed by symptoms of venous thromboembolism, a conclusion not supporting the concept that by decreasing such symptoms, thromboprophylaxis may improve a patient's quality of life.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, a Cochrane review of randomized controlled trials showed that pharmacologic VTE prophylaxis reduced deep vein thrombosis and increased major bleeding events, but had no significant effect on mortality or pulmonary embolism in medical inpatients at risk of VTE. 6 At St Paul's Hospital, a large teaching hospital in Vancouver, British Columbia, initiation of thromboprophylaxis is guided by a regional, hospital-wide preprinted order (PPO; see Appendix 1, available at www.cjhp-online.ca/index.php/cjhp/issue/view/ 118/showToc). This PPO stratifies patients as having high, moderate, or low risk for VTE events and recommends thromboprophylaxis for all but low-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Both UH and LMWH significantly reduce the incidence of DVT in acutely ill medical patients, although they also increase the risk of serious bleeding without a clear effect on all-cause or PE-related mortality. However, LMWH has been found to cause less bleeding than UH in this context, and LMWH is also shown to have a greater effect on preventing DVT (Alikhan et al, 2014), although an earlier metaanalysis did not detect significant differences in DVT prevention or bleeding outcomes between UH-and LMWH-treated medical patients (Kanaan et al, 2007). UH and LMWH regimens are safe and effective in acutely ill medical patients, with the consensus being that LMWHs have an improved safety profile in this setting .…”
Section: Clinical Use As An Anticoagulant/ Antithromboticmentioning
confidence: 98%